Efeito do tratamento com óleo de coco na perda óssea de camundongos alimentados com dieta rica em gordura - Larissa Bernardes de Rezende (2020)
Obesity is characterized by the accumulation of body fat associated with low-grade chronic inflammation, which is related to an increased risk of developing bone loss, and consequently, osteoporosis. Dietary approaches are proposed to treat bone loss, however alternative treatments from foods are not yet widely explored. Virgin coconut oil (VCO) is a functional food due to its significant amount of medium-chain fatty acids. In recent years, VCO has been widely used as a possible treatment for several diseases, including Alzheimer's, heart disease, obesity, among others. However, knowledge about VCO supplementation in the treatment of bone loss is still incipient. This study aimed to evaluate the effect of dietary supplementation with VCO in treating bone loss in mice fed a high-fat (HF) diet. However, data about it in the treatment of bone loss are still very scarce. This study aimed to evaluate the impact of VCO administration as a treatment for bone loss in mice fed a high-fat (HF) diet. Male C57BL / 6 mice were initially divided into two groups and fed either the AIN93 control diet (C) or the HF diet for 8 weeks. At the 9th week, the mice fed the HF diet were regrouped into 4 groups until the 12th week: (i) HF diet; or HF diet supplemented with different doses of VCO, (iii) 1000mg / kg, (iv) 3000mg / kg or (v) 9000mg / kg. Although the weight gain between the groups did not differ, the final body weight was higher in the HF group compared to the control group, but without changes in those treated with VCO. There was no significant difference in food intake between groups. When bone parameters were evaluated, the serum concentrations of RANKL, a bone loss marker, and OPG, as opposed to this signaling, did not change between the groups. However, only animals that received the medium dose of VCO showed a tendency towards a lower RANKL / OPG ratio, being the dose chosen to evaluate bone microarchitecture. In general, the HF group showed lower bone mineral density and bone volume, thinner trabeculae with greater space between them, characterizing depletion of the femur and maxilla's bone structure. Treatment with the medium dose of VCO worsened bone mineral density and trabecular separation in the animals' maxilla, but the bone loss already present in the femur was not altered. As expected, adiposity, area of adipocytes and serum leptin concentrations were higher in the group fed with HF diet compared to the control, but without change after the different treatments with the VCO, and with an increase in the area in those treated with the high dose of VCO. The glucose intolerance observed in the HF group was not altered with the addition of VCO to the HF diet, and they were also shown to be hyperglycemic. Although changed in the HF group, the serum concentrations of total cholesterol and triglycerides did not change with the treatments. Therefore, treatment with VCO in mice fed the HF diet does not seem to be beneficial for treating bone loss, obesity and even the associated metabolic disorders.